Management of the Implementation of Accounting Information System on the Expenditure Cycle at PT RZ - Arjani, Muftiyana Husna; Putri, Tiwi Venta; Sinambela, Reymond Eduard; Nurkamila, Jasmine; Ratnaningsih, Rini (Value : Journal of Management and Business, 2024)
This study discusses the implementation of the cash disbursement cycle at PT RZ, a manufacturing company engaged in the production and distribution of Napolly products in Indonesia. The focus of this research is the cash disbursement cycle, involving data such as goods receipt documents, purchase orders, and other related records. PT RZ has implemented an internal control system that serves as a safeguard to prevent undesirable events in the cash disbursement process. The findings of this study provide a detailed overview of (1) the functions involved in the cash disbursement cycle, (2) the documents and records used in the cash disbursement cycle, (3) the procedures of the cash disbursement cycle, and (4) the internal control system implemented by the company to ensure the effectiveness and security of cash disbursements.